PERANAN ORANG TUA DALAM PEMBENTUKAN KARAKTER DAN TUMBUH KEMBANG ANAK - Purnami Dewi, Luh Ayu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Childhood is a very important and valuable phase and is the period of formation in the period of human formation. Early childhood is often viewed as a golden age for education providers. The golden age of the child is a very fundamental phase for the development of the individual because in this phase there are great opportunities for the formation and development of a person. So great the role of parents in the formation of character and child development, it is natural if parents need to apply a balanced parenting (authoritative) in children, not authoritarian parenting or permissive.